Protection from articular damage by passive or active anti‐tumour necrosis factor (TNF)‐α immunotherapy in human TNF‐α transgenic mice depends on anti‐TNF‐α antibody levels. (11th March 2013) - Semerano, L.; Biton, J.; Delavallée, L.; Duvallet, E.; Assier, E.; Bessis, N.; Bernier, E.; Dhellin, O.; Grouard‐Vogel, G.; Boissier, M.‐C.
Summary Active anti‐tumour necrosis factor (TNF)‐α immunization with the kinoid of TNF‐α (TNF‐K) induces polyclonal anti‐TNF‐α antibodies and ameliorates arthritis in human TNF‐α (hTNF‐α) transgenic mice (TTg). We compared the efficacy of TNF‐K to that of infliximab (IFX) and of TNF‐K and IFX co‐administration, and evaluated whether the titres of anti‐hTNF‐α antibodies induced by immunization were a determinant of TNF‐K efficacy. Forty‐eight TTg mice received one of the following treatments: TNF‐K immunization (TNF‐K group); weekly IFX throughout the study duration (IFXw0–15); TNF‐K plus weekly IFX for 4 weeks (TNF‐K + IFX); and weekly IFX for 4 weeks (IFXw0–4); PBS. Animals were killed at week 16. Anti‐hTNF‐α antibody titres and clinical and histological scores were compared. All TNF‐K immunized mice (TNF‐K and TNF‐K + IFX) produced anti‐hTNF‐α antibodies. Titres were higher in TNF‐K versus TNF‐K + IFX (P < 0·001) and correlated inversely with histological inflammation (R = −0·78; P = 0·0001) and destruction (R = −0·67; P = 0·001). TNF‐K + IFX had higher histological inflammation and destruction versus TNF‐K (P < 0·05). A receiver operating characteristic (ROC) analysis of anti‐hTNF‐α antibody titres identified the criterion cut‐off value to discriminate most effectively between the TNF‐K and TNF‐K + IFX groups. Mice with high versus low titres had less histological inflammation and destruction (P < 0·05). In a model of TNF‐α‐dependent arthritis, protection from articular damage by TNF‐K correlates with the titres of induced anti‐hTNF‐α antibodies. The co‐administration of TNF‐K and a short course of infliximab does not result in less articular damage versus solely TNF‐K, due probably to lower anti‐hTNF‐α antibody production. These results are relevant for future development of active anti‐TNF‐α immunization in human disease.